2006
DOI: 10.1542/peds.2005-1129
|View full text |Cite
|
Sign up to set email alerts
|

Endemic Iron Deficiency Associated With Helicobacter pylori Infection Among School-Aged Children in Alaska

Abstract: OBJECTIVES. Rural Alaska Natives have a high prevalence of iron deficiency and Helicobacter pylori infection. The objective of this study was to estimate the prevalence of iron deficiency, iron-deficiency anemia, and active H pylori infection among school-aged children in rural Alaska.METHODS. We enrolled 68% (688) of the 7-to 11-year-old children from 10 predominantly Alaska Native villages in southwestern Alaska. We collected venous blood samples to assess iron deficiency and anemia. Each child was tested fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
119
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(136 citation statements)
references
References 37 publications
7
119
2
2
Order By: Relevance
“…The 45?4 % prevalence of H. pylori exposure observed in the present study is high and consistent with other studies of Canadian First Nations and Inuit and Alaskan native children (6,16,24,25,45) . In contrast, lower rates of H. pylori exposure have been reported (5?5-7?1 %) for American and Canadian children (19,46) .…”
Section: Discussionsupporting
confidence: 93%
“…The 45?4 % prevalence of H. pylori exposure observed in the present study is high and consistent with other studies of Canadian First Nations and Inuit and Alaskan native children (6,16,24,25,45) . In contrast, lower rates of H. pylori exposure have been reported (5?5-7?1 %) for American and Canadian children (19,46) .…”
Section: Discussionsupporting
confidence: 93%
“…A recent description of work undertaken several years ago in Alaska found that H. pylori IgG seropositivity was associated with Fe-deficiency anaemia, whereas in the same subjects, H. pylori detected by 13 C-UBT or faecal antigen test was not (55) . This contrasts with the findings of another large population study among Alaskan Natives (20) , and encourages a cautious approach to interpreting the results of these data. Several authors have suggested that H. pylori may cause Fe deficiency.…”
Section: Discussioncontrasting
confidence: 78%
“…This was in agreement with Baggett et al, [22] who reported that H. pylori infection was associated with older age and the association between iron deficiency and H. pylori infection was modified by age, with the strongest association in children who were aged ≥9 years. The increased risk in older children seems biologically reasonable as older children are likely to have been infected for longer than younger children, allowing more time for iron deficiency to develop.…”
Section: Resultssupporting
confidence: 92%